THE EFFECTIVENESS OF THE TEAM GAMES TOURNAMENT LEARNING MODEL BASED ON VIRUS MATERIAL EXPLORATION ON STUDENT LEARNING OUTCOMES - DIAN HANJAYANI (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2022)
Some indicators of the emergence of learning motivation include the desire to succeed, encouragement and need in learning, future hopes and aspirations, appreciation in learning, interesting activities in learning and a conducive learning environment that allows students to learn well, the learning outcomes of class X students have not yet reached with a completion limit value of 70. One of the lessons learned to overcome this problem is to apply the exploration-based Team Games Tournament (TGT) learning model.The research was conducted using an experimental method with a one shot case study design. The population of the study was grade X students of SMAN. The research sample was taken by using convenience sampling technique. While the data analysis is quantitative and descriptive qualitative. The results showed that the level of student activity in the three meetings were 96.76%, 96.77% and 100% of X MIPA 1 class students in the high and very high activity categories. In class XMIPA2 the percentage of activity in three meetings was 68.75%, 78.15% and 97.25% in the high and very high activity categories. Meanwhile, in the XMIPA3 class the percentages of activity were 62.27%, 76.03% and 97% in the high and very high activity categories. The results of the analysis of learning outcomes showed the average value of learning outcomes in class X MIPA1 reached 84.2; class X MIPA 2 reached 78.08 and class X MIPA 3 reached 79.15.Based on the results of the study, it was concluded that the application of the exploration-based TGT learning model on Virus material on the learning outcomes of class X students at SMAN 1 Tanggul was effective in optimizing student learning outcomes and activities.